KEBIJAKAN POLITIK PAI DALAM BINGKAI REGULASI DI INDONESIA - Nawazir, Safrudin; Aprison, Wedra (Jurnal Penelitian Ilmu Pendidikan Indonesia, 2022)
This paper discusses the political policies of Islamic Religious Education within the regulatory framework in Indonesia. Islamic Religious Education in general is included in the national curriculum in all schools, both public and religious schools. This writing uses the method of literature study. The conclusions from this writing are 1) Law Number 20 of 2003 concerning the National Education System has regulated the position of Islamic Education. In this Law, the position of Islamic Education is regulated as a subject and as a Sub-System of National Education, 2) Regulations in Indonesia as a source of formal law in the form of laws and regulations which have several elements, namely a written decision formed by state institutions or authorized official, and binding on the general public, 3) Government Regulation Number 55 of 2007 concerning Religious Education and Religious Education which makes Islamic education regulations increasingly clear in the Indonesian legal system.